KAJIAN FAKTOR PSIKOLOGI YANG BERPOTENSI MEMPENGARUHI KEBERHASILAN RUKYAT - Ridhokimura Soderi; Ahmad Izuddin (JURIS (Jurnal Ilmiah Syariah), 2020)
The success factor in hilal is not only related to astronomical aspects. However, it is also closely related to perukyat’s psychological itself. In psychology, experience is one aspect studied as a scientific study of behavior and mental processes. Psychology uses a systematic method to observe human behavior and draw conclusion from this observation. Some psychological aspects of the perukyat are vision, perception, attention, concentration, and experience. Thorndike's law effect theory states that if an action is followed by a satisfactory change in an environment, the possibility of that action to be repeated tends to increase. That experience is an ability to decide on something because of the knowledge that has been obtained previously. In everyday human life, human experience always forms a unity in certain patterns and configurations. The rukyat technique used by Inwanuddin is in line with psychological theories, namely rukyat before ghurub which aims to increase concentration, then many experiences also affect the subsequent results of rukyat. Some levels of experience obtained based on the data and results of the interval class calculation are: 1-5 times is less experienced, 6-10 times sufficient experience, 11-15 times experienced, 16-20 times very experienced.